User emotional interaction processor: a tool to support the development of GUIs through physiological user monitoring - Pinto, Duarte Maria Stock da Cunha Santiago (2021)
Ever since computers have entered humans' daily lives, the activity between the human and the digital ecosystems has increased. This increase encourages the development of smarter and more user-friendly human-computer interfaces. However, to test these interfaces, the means of interaction have been limited, for the most part restricted to the conventional interface, the "manual" interface, where physical input is required, where participants who test these interfaces use a keyboard, mouse, or a touch screen, and where communication between participants and designers is required. There is another method, which will be applied in this dissertation, which does not require physical input from the participants, which is called Affective Computing. This dissertation presents the development of a tool to support the development of graphical interfaces, based on the monitoring of psychological and physiological aspects of the user (emotions and attention), aiming to improve the experience of the end user, with the ultimate goal of improving the interface design. The development of this tool will be described. The results, provided by designers from an IT company, suggest that the tool is useful but that the optimized interface generated by it still has some flaws. These flaws are mainly related to the lack of consideration of a general context in the interface generation process.